[N `-(5-Bromo-2-oxidobenzylidene-kappa O)-3-hydroxy-2-naphthohydrazidato-kappa N-2 `,O]dicyclohexyltin(IV) - Lee, S.M.; Ali, H.M.; Lo, K.M. (International Union of Crystallography, 2010)
The environment at the Sn-IV atom in the title compound, [Sn(C6H11)(2)(C18H11BrN2O3)], is distorted trigonal-bipyramidal, with the two cyclohexyl groups and the imino N atom forming the equatorial plane. The axial O-Sn-O angle is 155.97 (9)degrees. The presence of an intramolecular O-H center dot center dot center dot N hydrogen bond in the Schiff base ligand helps to stabilize the overall structure.